Burnout and Quality of Life: A Cross-Sectional Study of Dental Clinic Employees at Dent Smile Jakarta - Febrina Emanuela; Awwalunisa Aprilia Wijaya; P. Purwadi; Yani Restiani Widjaja (Manunggal Halim Jaya, 2024)
Quality of life is an individual's assessment of their life, which can be influenced by burnout. Burnout is a work-related stress syndrome characterized by emotional exhaustion, a sense of low achievement, and depersonalization. This condition can negatively impact the quality of service, performance, and overall health of clinic employees. The objective of this study is to examine the relationship between burnout and quality of life among employees at the Dent Smile Dental Clinic in Jakarta. The research design employed is a descriptive correlational method with a cross-sectional approach. The sampling technique utilized is purposive sampling. The study's findings indicate that among the 60 employees at the Dent Smile Dental Clinic in Jakarta, 19 employees (31.7%) exhibited low levels of burnout, 17 employees (28.3%) displayed moderate burnout, 10 employees (16.7%) experienced relatively high burnout, and 14 employees (23.3%) were categorized as having high burnout. Meanwhile, 38 employees (63.3%) were found to have a moderate quality of life, 10 employees (16.7%) had a high quality of life, and 12 employees (20%) had a very high quality of life. Data analysis using the Chi-square test revealed no significant relationship between burnout and quality of life among employees at the Dent Smile Dental Clinic in Jakarta (p = 0.633). It is recommended that future research explore other factors influencing burnout, such as length of service, age, and gender.